Allusions to the Cinematographic Space in the Twentieth Century Novel: The Case of Young Sanchez (1957), by Ignacio Aldecoa - Valverde Maestre, Águeda María; Pérez-Rufi, José Patricio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The relationships between literature and cinematography stand out for the baggage of the literary. In the 1950s, Spanish writers begin to include audiovisual mentions. The objective of this study is to analyze the cinematographic codes related to the construction of space in the story of Young Sánchez (1957) from an intermedial perspective. For this, the Chatman methodology is applied. Likewise, the statements of Casetti and Di Chio are reviewed, describing the results obtained from the perspective of audiovisual analysis. This research places Ignacio Aldecoa as a film writer and his audience as literary spectators.